BACK PAIN ASSOCIATED WITH OSTEOPOROSIS — TREATMENT PATTERNS, APPROACHES TO THERAPY - N. A. Shostak; N. G. Pravdyuk (Klinicist)
The article highlights current approaches to diagnosis and treatment of back pain, associated with osteoporosis. An algorithm for management of patients with vertebral compression fracture, complicated by pain, the main approaches to drug treatment of back pain and osteoporosis are described.